Analisis Implementasi Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta Sebagai Instrumen Pelestarian Dan Perlindungan Tari Tradisional Dari Ancaman Klaim Budaya Oleh Negara Asing - Putri, A.A.Sg. Manik Maharani; Sudharma, Kadek Januarsa Adi (Consensus : Jurnal Ilmu Hukum, 2025)
Indonesia is rich in culture and traditions. One of them is traditional dance, which reflects the cultural wealth and serves as evidence of the unique diversity of Indonesian society. This study aims to discuss the implementation of Law No. 28 of 2014 on Copyright as an instrument for the preservation and protection of traditional dance from the threat of cultural claims by foreign countries. The method used in this research is normative juridical, by examining primary, secondary, and tertiary legal materials, such as legislation, journals, academic literature, and court decisions. The analysis and findings show that Article 28 of 2014 and Article 38 of the Copyright Law provide a strong legal basis for the state to hold copyrights over expressions of traditional culture. This includes regulating its use, legal prevention at the international level, and facilitating recognition by UNESCO in relation to traditional culture and cultural heritage. The challenges faced in this protection include a lack of public awareness, budget limitations, international legal challenges, and limited access for indigenous Indonesian communities to legal protection, which must be supported by the government and authorized institutions. Therefore, strategic steps such as digitization, data strengthening, inventory, international cooperation, and cultural promotion are required to provide more effective protection of traditional dance and prevent cultural claims by other countries.